ETIKA INDIVIDU DAN ORGANISASI DALAM BISNIS - Masruchin (Istithmar: Jurnal Studi Ekonomi Syariah, 2018)
Business is a business activity wich is conducted by individuals and organizations for produce and sell goods or services in order to get profit to fulfill basic needs of society. In business by individuals and organizations nowadays are also influenced by moral values so that resulting different economic behavior or especially who applying the moral principles in business. The emergence of the discourse of business ethics thought was encouraged by business reality who ignore moral or moral values. From some parts, business is human economic activity that looking for profit only. Therefore, anything methods may be used to achieve that goal. The moral aspect of business competition, is considered an obstacle to success. In other side, business activity intended to seek the biggest profit, while the moral principles “limiting” business activity. Competition in the business world is capital strength competiton. Businessmen with big capital try to enlarge the reach of his business, so that small businessmen (small financier) are getting dragged. Similarly collusion practice, corruption, and nepotism (KKN) have played an important role in theat process. A prolonged monetary crisis in Indonesia, in fact can’t be released from the process of such economic activity, namely the depletion of moral values in its activitiess. Contrast with first group, the second group argues that business can be united with ethics. These circles reasoned that ethics are rational reasons for all human actions in all aspects of life, business aspects are no exception. The thinking of business ethic in islam ccurrently surfacing, on the grounds that Islam is a perfect religion. It’s a collection of rules of doctrine and values wwhich can deliver humans in their life toward the goal of happiness in life both in the world and the hereafter. Islam is a religion that provide a integrated way of life on the rules of social, cultural, economic, civil and political aspects. It’s also a system for all aspects of life, including the spiritual system as well as the system of economic behavior.